We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
405
1
avatar+1129 

Which statement best reflects the solution(s) of the equation?

x / x−1 − 1 / x−2   =   2x−5 / x^2−3x+2

 

A - There are two solutions: x = 2 and x = 3.

 

B- There is only one solution: x = 3.
The solution x = 2 is an extraneous solution.

 

C -There is only one solution: x = 3.
The solution x = 1 is an extraneous solution.

 

D - There is only one solution: x = 4.
The solution x = 1 is an extraneous solution.

 Oct 19, 2018

Best Answer 

 #1
avatar
+1

Solve for x:
x/(x - 1) - 1/(x - 2) = (2 x - 5)/(x^2 - 3 x + 2)

Multiply both sides by x^2 - 3 x + 2:
1 - x + x (x - 2) = 2 x - 5

Expand out terms of the left hand side:
x^2 - 3 x + 1 = 2 x - 5

Subtract 2 x - 5 from both sides:
x^2 - 5 x + 6 = 0

The left hand side factors into a product with two terms:
(x - 3) (x - 2) = 0

Split into two equations:
x - 3 = 0 or x - 2 = 0

Add 3 to both sides:
x = 3 or x - 2 = 0

Add 2 to both sides:
x = 3 or x = 2

x/(x - 1) - 1/(x - 2) ⇒ 2/(2 - 1) - 1/(2 - 2) = ∞^~
(2 x - 5)/(x^2 - 3 x + 2) ⇒ (2 2 - 5)/(2 - 3 2 + 2^2) = ∞^~:
So this solution is incorrect

x/(x - 1) - 1/(x - 2) ⇒ 3/(3 - 1) - 1/(3 - 2) = 1/2
(2 x - 5)/(x^2 - 3 x + 2) ⇒ (2 3 - 5)/(2 - 3 3 + 3^2) = 1/2:
So this solution is correct

The solution is: x = 3      The answer is "B"

 Oct 19, 2018
 #1
avatar
+1
Best Answer

Solve for x:
x/(x - 1) - 1/(x - 2) = (2 x - 5)/(x^2 - 3 x + 2)

Multiply both sides by x^2 - 3 x + 2:
1 - x + x (x - 2) = 2 x - 5

Expand out terms of the left hand side:
x^2 - 3 x + 1 = 2 x - 5

Subtract 2 x - 5 from both sides:
x^2 - 5 x + 6 = 0

The left hand side factors into a product with two terms:
(x - 3) (x - 2) = 0

Split into two equations:
x - 3 = 0 or x - 2 = 0

Add 3 to both sides:
x = 3 or x - 2 = 0

Add 2 to both sides:
x = 3 or x = 2

x/(x - 1) - 1/(x - 2) ⇒ 2/(2 - 1) - 1/(2 - 2) = ∞^~
(2 x - 5)/(x^2 - 3 x + 2) ⇒ (2 2 - 5)/(2 - 3 2 + 2^2) = ∞^~:
So this solution is incorrect

x/(x - 1) - 1/(x - 2) ⇒ 3/(3 - 1) - 1/(3 - 2) = 1/2
(2 x - 5)/(x^2 - 3 x + 2) ⇒ (2 3 - 5)/(2 - 3 3 + 3^2) = 1/2:
So this solution is correct

The solution is: x = 3      The answer is "B"

Guest Oct 19, 2018

34 Online Users

avatar
avatar